Fluorescence Spectroscopy. Issue 10 (1st May 2015) - Lee, Claudia Y.
Abstract: Fluorescence is an extremely powerful tool in modern biology, physics, and chemistry laboratories. This unit begins with the physics of fluorescence, the biological applications of fluorescence, and the mechanisms behind spectrometers and fluorometers, followed by strategies to choose an appropriate fluorophore according to the instrumentation at hand. The first part of the unit walks the reader through the acquisition of an absorption spectrum and explains how it can be used to measure the degree of labeling on conjugated proteins. The discussion then extends into how to obtain fluorescence emission spectra, which can be utilized as fluorescence indicators for protein detection. © 2015 by John Wiley & Sons, Inc.